Nesting of the snowy plover (Charadrius nivosus) in Atotonilco, Jalisco, Mexico - Quintero-Félix, Raúl Said (2022)
The snowy plover (Charadrius nivosus) is one of the least abundant shorebirds. It is an endangered species whose populations are in steady decline. Mexico is important for the populations of this species, but there is little information on its reproduction and threats. To obtain data on nesting and potential threats, we monitored the snowy plover population at Atotonilco Lagoon during the breeding season (March-July) in 2020. We conducted counts of individuals and nests, clutch size, approximate egg-laying date, and observations on threats present during this period. Males represented 85% (n = 140) of the total population and the month with the highest number of nests was May (n = 15). The average nest size was 2.5 eggs. Water surface area was variable during the sampling months, but it was not statistically proven that the greater the desiccation, the smaller the nest size (p = 0.09). The main threats identified were motorized vehicles and livestock. The Atotonilco Lagoon is a key site for snowy plover reproduction and management actions should be implemented to increase the presence of water and regulate human activities.